The Model of Optimization for Parameter in the Mixing Process of Water Treatment / Mastiadi Tamjidillah...[et al.] - Tamjidillah, Mastiadi; Budi Santoso, Purnomo (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
This research aims to determine the optimized model of raw water mixing process having a high turbidity level, alum or Poly Aluminium Chloride (PAC) and pump stroke to input the raw water taken from river. It is to obtain the proportional composition and the optimized model for the setting of parameter with the experimental design of Taguchi method in which the process of mixing water such as 5lt/sec, 10lt/sec, and 15lt/sec and % of alum water 5 ppm, 10 ppm, and 15 ppm with the installations of pump stroke that are of 15 %, 20 % and 25 %. The dominant factor which influences the average response is beneficial to choose the level of factor producing quality of clean water and optimal mixing model. Model produced from this process can be used as basis to find out the characteristic of raw water supply, and design the mixing process of optimal alum dosage and the behavior of floating particles (flock). The particles were later processed in SEM (Scanning Electron Microscope) to uncover the microstructure content of sedimentation result of the mixing process. With the finding of proportional setting for parameter of raw water supply, it thus results clean water which is proportional to the quality standard.